2018
DOI: 10.3390/min8020035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Copper Sulfide Nanoparticles Using Biogenic H2S Produced by a Low-pH Sulfidogenic Bioreactor

Abstract: Abstract:The application of acidophilic sulfate-reducing bacteria (SRB) for the treatment of acidic mine water has been recently developed to integrate mine water remediation and selective biomineralization. The use of biogenic hydrogen sulfide (H 2 S) produced from the dissimilatory reduction of sulfate to fabricate valuable products such as metallic sulfide nanoparticles has potential applications in green chemistry. Here we report on the operation of a low-pH sulfidogenic bioreactor, inoculated with an anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Covellite exhibits semiconductor properties and can be used in photocatalytic reactions [25], as a semiconductor [22], in solar cells [26], as adsorbents [25], and in electronic devices. Recently, Colipai and colleagues [27] described the synthesis of copper nanoparticles from a copper sulfate solution (2 mM CuSO 4 ) in the presence of a citrate buffer (pH 6.0) by biosulfidogenesis, opening a new frame for potential covellite applications in the development of nanostructures such as, nanotubes, nanoplatelets, and nanowires [28]. Copper nanoparticles have been chemically synthetized from CuSO 4 .5H 2 O solution in the presence of ascorbic acid (surface agent), sodium borohydride (reducing agent), and sodium hydroxide (pH adjust) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Covellite exhibits semiconductor properties and can be used in photocatalytic reactions [25], as a semiconductor [22], in solar cells [26], as adsorbents [25], and in electronic devices. Recently, Colipai and colleagues [27] described the synthesis of copper nanoparticles from a copper sulfate solution (2 mM CuSO 4 ) in the presence of a citrate buffer (pH 6.0) by biosulfidogenesis, opening a new frame for potential covellite applications in the development of nanostructures such as, nanotubes, nanoplatelets, and nanowires [28]. Copper nanoparticles have been chemically synthetized from CuSO 4 .5H 2 O solution in the presence of ascorbic acid (surface agent), sodium borohydride (reducing agent), and sodium hydroxide (pH adjust) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Among the existing EES devices, there is a complementary relationship between metal-ion batteries (MIBs) and supercapacitors (SCs) since the former has a high energy density, but the latter can deliver extreme power density [1][2][3][4][5]. It is recognized that increasing the power energy of the MIBs to as high as that of the SCs is intrinsically challenging, owing to the insertion/extraction of the metal ions from the corresponding electrode materials being principally essential, that is, the energy storage mechanism [6][7][8][9][10]. On the contrary, it has been demonstrated that several electrode materials that followed a redox reaction can provide more capacitances as compared with the traditionally used carbonaceous materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the removal of Fe and Ni was lower than 90% and higher than 80% in both reactors, respectively. In addition, copper nanoparticle production with a particle size of ~50 nm was achieved using the BSP process treating an AMD synthetic solution [15]. The possibility to generate products with high values directly from waste sources should increase in further research of metal sulfide precipitation.…”
Section: Acid Mine Drainages (Amd)mentioning
confidence: 99%